SELF-GOVERNING LEARNING STRATEGIES (EDUCATION IN THE 21ST CENTURY, 2023)
Self-directed learning strategies are based on theories of the development of emotional intelligence, which studied the mechanism of controlling emotions, signals and stimuli. Research has shown that skills are best performed when there is high motivation, hard learning, and feedback. Learning is a key factor in building new neural connections. High motivation plays a critical role in the development of emotional intelligence. The development of emotional intelligence is possible only with a sincere desire and intense effort. The development of emotional intelligence is based on self-directed learning - the purposeful development or strengthening of certain qualities of a person as he is and / or wants to be. In connection with the above, this article discusses strategies for self-directed learning based on a competent approach. In connection with the above, this article discusses strategies for self-directed learning based on a competent approach.
Keywords: Keywords: Self-study, self-study model, learning effectiveness concept, career planning learning strategy.